Assessing Peru’s Land Monitoring System Contributions towards Fulfilment of Its International Environmental Commitments - (:unkn) unknown (MDPI, 2024)
Land use change (LUC) is recognized as one of the major drivers of the global loss of biodiversity and represents a major threat to ecosystems. Deforestation through LUC is mainly driven by fire regimes, logging, farming (cropping and ranching), and ille...
Keywords: Monitoreo ambiental; Compromisos internacionales